The gift of tongues: women's xenoglossia in the later middle ages - Cooper-Rompato, Christine F. (Pennsylvania State Univ. Press, 2010)
Explores the phenomenon of xenoglossia, the sudden, miraculous ability to speak, understand, read, or write a foreign language, as it appears in the later medieval hagiographic record and in English literature. Includes discussion of the late medieval English writers Geoffrey Chaucer and Margery Kempe --Provided by publisher